PERANCANGAN FILTER PASIF UNTUK MEREDAM HARMONISA YANG DI BANGKITKAN OLEH BEBAN LAMPU HEMAT ENERGI (LHE) - Oka Darma Putra, I Kadek; Wijaya, I Ketut; Mataram, I Made (Jurnal SPEKTRUM; Vol 6 No 3 (2019): Jurnal SPEKTRUM, 2019)
The load in the form of energy saving lamps has a harmonic loss generated. The harmonic effect generated is caused by the use of non-linear power electronic components, resulting in a current that is made into a distorted sinusiodal wave which results in the formation of waves at multiple multiples of the fundamental frequency. Based on the negative impact caused by the energy saving light, the filter was designed to reduce the THDi percentage generated by the energy saving light, by installing a low pass RC filter on the energy saving light.